On possibility of short-living positron-emitting nuclides production using electron accelerator for medical diagnostics - Zadvorny, A.S. (Вопросы атомной науки и техники, 2011)
Comparison is made of technologies of radiopharmaceuticals (RPC) production that are labeled with positron-emitting nuclides using a cyclotron and an electron accelerator (EA). It is shown that specific activities of RPC produced on EA are sufficient for the g-camera and PET diagnostics.